Baicalin Protects Mice Brain From Apoptosis in Traumatic Brain Injury Model Through Activation of Autophagy - Fang, Jiang; Zhu, Yihao; Wang, Handong; Cao, Bailu; Fei, Maoxing; Niu, Wenhao; Zhou, Yuan; Wang, Xiaoliang; Li, Xiang; Zhou, Mengliang (Frontiers in Neuroscience, 2019)
Autophagy has been implicated with the secondary injury of traumatic brain injury (TBI) and is expected to be a therapeutic target. Baicalin, a neuroprotective agent, has been proven to exert multi-functional bioactive effects in brain injury diseases. however, whether Baicalin influences autophagy after TBI has not been investigated. In the present study, we aimed to explore the effects of Baicalin on TBI in mice model, and focused on autophagy as a potential mechanism. We found that Baicalin administration significantly improved motor function, reduced cerebral edema, and alleviated disruption of blood-brain barrier (BBB) after TBI. Besides, TBI-induced apoptosis was reversed by Baicalin evidenced by Nissl staining, terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) assay, and the level of cleaved caspase 3. More importantly, Baicalin enhanced autophagy by detecting the autophagy markers (LC3, Beclin 1, and p62) using western blot and by LC3 immunofluorescence staining, thus ameliorating mitochondrial apoptosis evidenced by the decrease on translocation of Bax and cytochrome C following TBI. However, simultaneous treatment with 3-MA inhibited Baicalin-induced autophagy and abolished its protective effects on mitochondrial apoptotic pathway. In conclusion, we demonstrated Baicalin enhanced autophagy, ameliorated mitochondrial apoptosis and thus protecting mice brain in TBI mice model.